Gestión de recuperación de cartera de crédito vencida de la Cooperativa de Ahorro y Crédito San Antonio sucursal La Unión durante el periodo fiscal 2021. - Rivera Tomalá, Gustavo Víctor (2022)
The San Antonio credit cooperative is a financial institution dedicated to providing services and credit management for its members. It is a private entity that has its parent company in setting it up and its agency in the La Unión parish. The credit portfolio comprises the backbone of the activity to which the institution is dedicated, since by placing money in the different sectors through different types of credit offered by the cooperative to its members, it receives the interest with which it can continue financing and finishing their work. The recovery of the credit portfolio placed is essential for the liquidity of the financial institution since if the amount placed is not recovered, this will lead to economic difficulties and will put the solvency of the financial institution at risk. It is very important to determine the collection strategies of the placed portfolio and to apply them in the correct way in order to reduce and mitigate the risk that an overdue portfolio will ultimately become an uncollectible portfolio ascending to the financial coffers of the entity. the management of the credit portfolio must be in charge of a credit manager and the different advisers, in addition to the person in charge of collecting said credits, there must be policies and guidelines to grant these credits and to guarantee their recovery once the periods agreed between the partner and the institution are complied with.